2020
DOI: 10.1039/c9ra09579a
|View full text |Cite
|
Sign up to set email alerts
|

A reliable chemiresistive sensor of nickel-doped tin oxide (Ni-SnO2) for sensing carbon dioxide gas and humidity

Abstract: Herein, we report the chemiresistive gas and humidity sensing properties of pristine and nickel-doped tin oxide (Ni-SnO2) gas sensors prepared by a microwave-assisted wet chemical method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 63 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Meanwhile, Ni could be doped into the metal Sn to change surface properties for the improvement of adsorption. , With the addition of nickel elements, the performance is improved and the properties are enlarged. Furthermore, doping Ni could cause smaller sizes of nanostructure, and the performance of adsorption has been enhanced . Materials of Ni-doped Sn with high specific surface area nanostructures containing magnetic metal nickel are promising in adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Ni could be doped into the metal Sn to change surface properties for the improvement of adsorption. , With the addition of nickel elements, the performance is improved and the properties are enlarged. Furthermore, doping Ni could cause smaller sizes of nanostructure, and the performance of adsorption has been enhanced . Materials of Ni-doped Sn with high specific surface area nanostructures containing magnetic metal nickel are promising in adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, doping Ni could cause smaller sizes of nanostructure, and the performance of adsorption has been enhanced. 9 Materials of Ni-doped Sn with high specific surface area nanostructures containing magnetic metal nickel are promising in adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…The tiny variation in SPR angle is caused due to change in the concentration of the CO 2 gas molecules,and the changes in its physical condition from the reference value. Other techniques that are also reported for CO 2 gas sensing includes chemiresistive sensor of nickel‐doped tin oxide (Ni‐SnO 2 ) for sensing CO 2 and humidity [21]; another work presents polymer composite‐based chemiresistive type carbon dioxide (CO 2 ) gas sensors using different degree of sulfonated poly (ether ether ketone) (SPEEK) incorporated with diethanolamine (DEA)‐functionalised multi‐wall carbon nanotubes (d‐MWCNTs) [22]. In another work, low‐temperature hollow nanostructured CeO 2 ‐based sensor for CO 2 detection was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that these spinel oxides are better catalysts on account of their activity and stability. The phenomenon of synergism in two or three metal-based catalysts is a fascinating aspect of catalytic research [15].…”
Section: Introductionmentioning
confidence: 99%